Agile business analysis : enabling continuous improvement of requirements, project scope, and agile project results - Aguanno, Kevin; Schibi, Ori (Plantation, FL : J. Ross Publishing, 2019)
Agile Business Analysis discusses trends in the business analysis and agile environments, how these two areas align and promote each other, and identifies areas of responsibility and ownership for the business analyst (BA). Readers will learn ways BAs can provide support to agile projects through modeling techniques; documentation; communication, meetings and reporting; governance; building user stories, elaborating requirements, and facilitating the estimating process; ensuring effective application of lessons, improvements, and efficiencies; and much more. The book is designed for BAs of all levels, from all types of environments.
1.Introduction to agile and agile processes -- 2.Agile challenges -- 3.Roles and responsibilities -- 4.Agile requirements and user stories -- 5.Agile documentation -- 6.The BA role in planning and estimating -- 7.Agile events and work products -- 8.Testing and solution evaluation -- 9.A day in the life of an agile business analyst -- 10.Moving forward.
Includes index.
Keywords: BUSINESS ANALYSTS; BUSINESS PLANNING; AGILE SOFTWARE DEVELOPMENT